Kopi Senja Cafe business plan report / Muhammad Irfan Naqiuddin Talib ... [et al.] - Talib, Muhammad Irfan Naqiuddin; Muizuddin, Muhammad Fathurrahman; Jailan, Muhamad Arif; Iskandar, Muhammad Arif Imran; Muhammed Hakiman, Amir Redzuan (2023)
KOPI SENJA CAFÉ distributed these coffee-based cafes to attract customers with our various coffees such as Americano, Coffee Latte, Cappuccino, Caramel Macchiato, Maroccino, and the most important part is our specialty menu of Blonde Coffee. Besides that, we also provide some pastries such as a cream cheese bagel and blueberry muffins. We chose to manufacture these products because people nowadays enjoy visiting cafes that serve a variety of delectable appetizers and coffees. KOPI SENJA CAFÉ products are also made with high-quality ingredients. We buy from supplier relationships that provide high-quality products at affordable prices. As a result, it will benefit both parties as customers will receive premium goods from our café, and at the same time, we will also get a lucrative profit. We also have high-quality raw materials such as flour, sugar, eggs, milk, and coffee. Besides that, KOPI SENJA CAFE also provides additional services to our customers such as online purchases that include delivery services, this makes it easier for customers who want to buy products from our cafe from their current location. We strive to achieve our concept by providing high-quality packages because we value customers as opposed to making huge profits. KOPI SENJA CAFÉ is located at 47 Jalan Plumbum, P7/P, Seksyen7, 40000, Shah Alam. Our competitors were RichiAmmo Coffee, Starbucks, and Kopi Saigon. Each of them has a unique skill set. This business started on the 1st January 2023 which the partners of the business has just done with their diploma. In order to market our products to consumers, our cafe must create a product strategy that includes a brand name, labeling, after-sales service, and delivery service. Then, as part of our marketing strategy, we will use social media sites such as Instagram, Facebook, and Twitter, as well as free testers. This will not only increase product sales but will also help to keep our cafe's reputation intact. The management team for Kopi Senja Café consists of 5 managers which are General Manager, Muhammad Irfan Naqiuddin, Administration Manager, Muhammad Fathurrahman, Financial Manager, Muhammad Arif Imran, Operation Manager, Amir Redzuan, and Marketing Manager, Muhamad Arif. The expected monthly sales of this business is RM45,669.10 which will make us able to pay for the cost of the business for a month. The sales forecast for the first year is RM548,029.20